The Southern snake-handling cult of the U.S.A - Shapcott, Moira (Department of Religious Studies, 2023)
At the turn of the Century, in the rural areas of the deep south, a small group of fundamentalists adopted the practice of confirming their faith by handling venomous snakes. Today the cult has spread to at least twelve different States, despite the fact that since 1947 snake handling has been prohibited by law in all states except one. The cult-members, however, regard the legislation as being a violation of their fundamental right to worship as they please. Fatalities occur, the leaders spend time in prison, but still the cult flourishes, with various congregations quite openly flouting the law. In addition to handling snakes, the cultists also drink poison and handle fire, according to their interpretation of the Bible.